2017
DOI: 10.7812/tpp/17-048
|View full text |Cite
|
Sign up to set email alerts
|

Finding Purpose: Honing the Practice of Making Meaning in Medicine

Abstract: Despite decades of advances in diagnosing and treating a broad range of illnesses, many changes in our health care system impede true caregiving, leaving patients and practitioners dissatisfied and creating an emotional burden for practitioners that contributes to the staggering rates of physician burnout. Given this dissatisfaction and disconnection, practitioners and patients alike can benefit from structured opportunities to explore the expectations, assumptions, and emotions that shape our understanding of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The authors concluded that group discussion, involving feedback and peer support, increased the value of the creative intervention in their study (Wallace et al, 2020). Leveen (2017) suggests that the mechanism by which poetry discussion strengthens interpersonal connections is through collaboration: 'deciphering' and 'working together to understand a poem'. Through the dynamics of a group discussion that starts with a focus on poetic form and language, challenging questions can arise and surprising insights can be located.…”
Section: Group Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors concluded that group discussion, involving feedback and peer support, increased the value of the creative intervention in their study (Wallace et al, 2020). Leveen (2017) suggests that the mechanism by which poetry discussion strengthens interpersonal connections is through collaboration: 'deciphering' and 'working together to understand a poem'. Through the dynamics of a group discussion that starts with a focus on poetic form and language, challenging questions can arise and surprising insights can be located.…”
Section: Group Discussionmentioning
confidence: 99%
“…Leveen (2017) suggests that the mechanism by which poetry discussion strengthens interpersonal connections is through collaboration: ‘deciphering’ and ‘working together to understand a poem’. Through the dynamics of a group discussion that starts with a focus on poetic form and language, challenging questions can arise and surprising insights can be located.…”
Section: Poetry As a Reflective Techniquementioning
confidence: 99%
“…10,16 Poetry provides a method of contemplation capable of exploring tolerance for different perspectives and promoting better understanding between practitioner and patient, among practitioners, and within health-care and society systems. 4,14,17,18 Poetry provides an instrument for patients and health-care professionals through which to find meaning in illness and grief 19 and as a mechanism to develop compassion and empathy for oneself and others. 5 Currently, the integration of humanities within medicine and health professions education lacks rigorous research evaluation.…”
Section: Introductionmentioning
confidence: 99%